Corporate Criminal Liability on Environmental Law: Indonesia and Australia - Aditya Wijaya, Muhammad; Alif Imam Dzaki (Jurnal Mulawarman Law Review, 2023)
Environmental damage is one of the major problems faced by Indonesia. It is a well-accepted fact that most cases of environmental damage in Indonesia are caused by the activities of large corporations. One of the measures adopted in overcoming environmental damage and ensuring accountability for violations of environmental law is through corporate criminal liability, in which companies can be held liable and be brought to criminal proceedings for violating environmental law. This paper seeks to discuss and analyse the legal regulation system of corporate criminal liability applied in Indonesia. The paper will delve into the nature of corporate criminal responsibility in accordance with the doctrines that underlie it, as well as actions that, in accordance with the law, would trigger the implementation of corporate criminal responsibility, the manners in which criminal responsibility would be attributable to a corporation, and the trial procedure for corporate criminal responsibility under the Indonesian judicial system. This paper seeks to bring light to the mechanism of the Indonesian environmental law in administering justice in cases of environmental law violations committed by corporations.